Online college English teaching-learning amidst Covid-19 pandemic: Opportunities, challenges, and solutions - Fujiono Fujiono; Nurul Hidayati; Desi Kurniati Agustina; Citra Siwi Hanayanti (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2022)
During Covid-19 outbreak, the lecturers and learners adjust to carry out class by applying online teaching-learning. Online teaching-learning built a new approach of communication between lecturers and learners in online course. This research aimed to describe online college English teaching-learning amidst Covid-19 pandemic: opportunities, challenges, and solutions. This research applied phenomenological research design in which the data sources were questionnaire and observation results dealing with the learners’ responses on teaching-learning amidst covid-19 emergency. It was found that almost all students studied English more accessible and flexible without came and met the lecturers in college, they could share information each other through online platform, nothing interaction among of them to prevent the outbreak. However, majority of college learners complained about financial, internet package, trouble networks, and time management that the learners sometimes got boring to study English. Dealing with the issues, Indonesia has contributed the internet package to assist the learners’ financial, and the lecturers has implemented games to create class more interactive, and energetic.DOI: 10.26905/enjourme.v7i1.6580